Probing spatial coupling of resistive modes in porous intercalation electrodes through impedance spectroscopy. Issue 7 (24th October 2018) - Mistry, Aashutosh N.; Mukherjee, Partha P.
Abstract : The spatial coupling between the pore-scale microstructural resistances and the electrode-scale measurements is detailed via a physics-based, mechanistic description. Abstract : In porous intercalation electrodes, coupled charge and species transport interactions take place at the pore-scale, while often observations are made at the electrode-scale. The physical manifestation of these interactions from pore- to electrode-scale is poorly understood. Moreover, the spatial arrangement of the constituent material phases forming a porous electrode significantly affects the multi-modal electrochemical and transport interplay. In this study, the relation between the electrode specification, resultant porous microstructure, and electrode-scale resistances is delineated based on a virtual deconvolution of the impedance response. Relevant short- and long-range interactions are identified. Without altering the microstructural arrangement, if the electrode thickness is increased, the resistances do not scale linearly with thickness. This dependence is also probed to identify the fundamental origins of thick electrode limitations.